The effect of lack of sleep on the recall activity of explicit semantic memory in children - Cherkaoui, Yassine (Journal of Educational and Psychological Sciences, 2022)
This study aimed to illustrate the lack of sleep effect (less than 7 hours) on the recall activity of explicit semantic memory in children, by comparing how many words each group could retrieve (8 children sleep less than 7 hours, 8 children sleep more than 8 hours). The performance of recall activity is compared between the two groups using the experimental method by comparing the number of words recalled by both groups. The study adopts the descriptive method to compare the two groups’ average values and standard deviations. Results show some differences regarding the efficiency of recall between the two groups: the group that slept for more than 8 hours managed to recall 85.41% of the total words learned, while the percentage of recall of the group that slept less than 7 hours is 72.91%. The study recommends that parents and caregivers pay attention to their children’s sleep quality and duration, as it impacts recall activity and other cognitive activities.